Optimizing the Patrol of the Sabhara Unit in Preventing Theft With Aggravated Circumstances in the Legal Area of the Sintang Police - Andryan Yoga Pratama (Indonesian Journal of Police Studies, 2021)
This research is motivated by the high number of criminal acts of theft with weights in Sintang Regency. The need for prevention efforts against the crime of theft by weight will be discussed in this study. In carrying out its duties, Article 13 of Law Number 2 of 2002 explains that the National Police of the Republic of Indonesia has the main task and function to overcome threats, challenges, disturbances, and obstacles in the form of potential disturbances, threats of disturbances, and real disturbances. In this study, the research literature used as a reference is a thesis from the Alumni Akpol (2018) Mega Ayundya which discusses the Blue patrol of the Sabhara Unit in preventing criminal acts of theft with weighting in Bandung district and Alumni Akpol (2018) Naufal syauqi who discusses the two-wheeled patrol in preventing theft by weight in Cianjur Regency. The concept used is the patrol concept and uses 6M management theory and crime prevention theory which will be discussed later in the discussion of research results. The research method uses a qualitative approach whose results are strengthened by the findings, observations, document studies, and interviews with information sources. The techniques used for data analysis include data reduction, data presentation, and drawing conclusions. The results of the study found that blue patrols to prevent drains were still not optimal with the regulations in Perkabaharkam number 1 of 2017 which had not been implemented and the analysis of management facilities that still had elements that hindered the implementation of blue patrols such as from the human side, money, materials, machines, methods, and equipment. market. Based on the results of the study, the researchers suggested that the leadership instruct members to carry out education and training as well as the use of the Whatsapp application to optimize the implementation of patrols in preventing theft by weighting in the Sintang Police Region.